Liquid crystal polymer powder, liquid crystal polymer film, and method for producing same

By producing liquid crystal polymer powder and fibrosis process with melt viscosity of 15 to 77 Pa·s, combined with the hot pressing process and papermaking method, the problem of insufficient fold resistance strength of the liquid crystal polymer film is solved, and high fold resistance and stability are achieved , suitable for high-frequency applications such as flexible circuit boards.

CN119278228APending Publication Date: 2025-01-07MURATA MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380042685.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

There is room for improvement in the fold resistance strength of the existing liquid crystal polymer films, especially in applications of flexible printed wiring substrates, which require higher fold resistance strength.

Method used

By producing liquid crystal polymer powder with a melt viscosity of 15 to 77 Pa·s, fibrosis is performed using a wet high-pressure crushing device to form fibrous particles, improving the MIT folding resistance and fracture tension of the liquid crystal polymer film, combining with the hot pressing process and The liquid crystal polymer film is manufactured by papermaking method to optimize its linear expansion coefficient and density.

Benefits of technology

It significantly improves the fold resistance and fracture tension of the liquid crystal polymer film, reduces the linear expansion coefficient, and is suitable for high-frequency circuit substrates such as flexible circuit boards and vibrating plates, enhancing its stability and durability in hot pressing treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278228A_ABST
    Figure CN119278228A_ABST
Patent Text Reader

Abstract

The liquid crystal polymer film with improved folding strength is obtained. The liquid crystal polymer powder contains fibrous particles comprising a liquid crystal polymer. And the melt viscosity of the liquid crystal polymer powder is 15-77 Pa.s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid crystal polymer powder, a method for producing the liquid crystal polymer powder, a liquid crystal polymer film, and a method for producing the liquid crystal polymer film. Background Art

[0002] In recent years, liquid crystal polymer (LCP) has attracted attention as a new substrate material for printed wiring corresponding to the next generation of high-speed transmission, as a material with less transmission loss and excellent high-frequency characteristics than before. Compared with polyimide resin, which is an existing substrate material, LCP has excellent low dielectric constant characteristics, high heat resistance and low water absorption, so it can reduce the loss of electrical signals, etc.

[0003] As a method for producing an LCP film for a printed wiring substrate or the like from a liquid crystal polymer, for example, a melt extrusion method and a solution casting method are known. The melt extrusion method is a method for forming a film by extruding a molten resin from an apparatus and bringing it into contact with a roller. The solution casting method is a method for forming an LCP film by applying a varnish obtained by dissolving an LCP raw material such as LCP particles in a solvent on a flat belt and drying it.

[0004] On the other hand, the manufacture method of fibrillar liquid crystal polymer powder is described in patent document 1. In this method, liquid crystal polymer (LCP) powder is first obtained by crushing the biaxially oriented film of liquid crystal polymer. Next, the obtained LCP powder is processed by using a wet high-pressure crushing device to manufacture fibrillar LCP powder. This fibrillar LCP powder can also be used as a raw material to manufacture LCP film. It should be noted that it is believed that the folding strength of the LCP film is improved by improving the bonding property of the fibrillar LCP particles after drying.

[0005] It should be noted that Patent Document 2 (Japanese Patent Publication No. 5-125160) discloses a resin composition composed of two segments and exhibiting liquid crystallinity, and states that the melt viscosity characteristics of the resin composition have a low temperature dependence and excellent moldability, and that the resin can be used to obtain a molded product with a good shape (a sheet with uniform thickness). Patent Document 2 states that the resin composition has a temperature of 245°C and a shear rate of 1000 seconds (sec -1 ) is 800 poise (80 Pa·s) or more.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 5904307

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 5-125160 Summary of the invention

[0010] When a liquid crystal polymer film is used as a substrate for printed wiring, for example, it is desirable to have high folding strength in order to improve the reliability of the printed wiring. In particular, when used as a substrate for flexible printed wiring, high folding strength is required. Therefore, there is room for further improvement in the folding strength of existing liquid crystal polymer films.

[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to obtain a liquid crystal polymer film having improved folding strength.

[0012] The liquid crystal polymer powder according to the first aspect of the present invention includes fibrous particles composed of a liquid crystal polymer. The liquid crystal polymer powder has a melt viscosity of 15 to 77 Pa·s.

[0013] The liquid crystal polymer film according to the second aspect of the present invention includes a liquid crystal polymer and has an MIT folding endurance of 100 times or more.

[0014] According to the present invention, the folding strength of a liquid crystal polymer film can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 These are photographs showing the liquid crystal polymer powders in Comparative Example 1 and Examples 1 to 9.

[0016] Figure 2 This is a graph showing the relationship between the melt viscosity and bulk density of liquid crystal polymer powders in Examples and Comparative Examples.

[0017] Figure 3 This is a graph showing the relationship between the melt viscosity of the liquid crystal polymer powder and the folding strength (MIT folding number) of the liquid crystal polymer film in Examples and Comparative Examples.

[0018] Figure 4 This is a graph showing the relationship between the melt viscosity of the liquid crystal polymer powder and the linear expansion coefficient (CTE) of the liquid crystal polymer film in Examples and Comparative Examples.

[0019] Figure 5 This is a flow chart showing a process for producing a liquid crystal polymer powder according to an embodiment.

[0020] Figure 6 It is a flowchart showing the manufacturing process of the liquid crystal polymer film of an embodiment.

[0021] Figure 7 1 is a flowchart showing a process for producing a fiber mat according to an embodiment.

[0022] Figure 8 This is a diagram showing a felting step of felting a liquid crystal polymer powder in the process of producing a fiber mat.

[0023] Fig. 9 This is a diagram showing the step of irradiating the second surface of the fiber mat with light. DETAILED DESCRIPTION

[0024] Hereinafter, a liquid crystal polymer powder and a liquid crystal polymer film according to one embodiment of the present invention will be described.

[0025] <Liquid crystal polymer powder>

[0026] A liquid crystal polymer (LCP) powder according to one embodiment of the present invention includes fibrous particles composed of a liquid crystal polymer.

[0027] Liquid crystal polymers are, for example, thermotropic liquid crystal polymers. Liquid crystal polymer molecules have a negative linear expansion coefficient (thermal expansion coefficient: CTE) in the axial direction of the molecular axis and a positive CTE in the radial direction of the molecular axis. It should be noted that liquid crystal polymers preferably do not have amide bonds.

[0028] As thermotropic liquid crystal polymers without amide bonds, for example, there can be cited copolymers of p-hydroxybenzoic acid, terephthalic acid and dihydroxybiphenyl (block copolymers of p-hydroxybenzoic acid and ethylene terephthalate) which have a high melting point and a low CTE and are called type 1 liquid crystal polymers, or copolymers (block copolymers) of p-hydroxybenzoic acid and 2,6-hydroxynaphthoic acid which are called type 1.5 (or type 3) and have a melting point between type 1 liquid crystal polymers and type 2 liquid crystal polymers.

[0029] (Melt viscosity)

[0030] The melt viscosity of the liquid crystal polymer powder is 15 to 77 Pa·s, preferably 20 to 77 Pa·s. As a result, the aspect ratio of the fibrous particles constituting the liquid crystal polymer powder is large (long fibrous), which can improve the folding strength of the liquid crystal polymer film produced using the liquid crystal polymer powder. In addition, the fiber felt produced using the liquid crystal polymer powder can also improve the breaking tension even if the temperature of the heat treatment is below the melting point of the liquid crystal polymer raw material. It should be noted that for the fiber felt, the porosity of the fiber felt can be adjusted by heating the temperature of the heat treatment to below the melting point of the liquid crystal polymer raw material.

[0031] It should be noted that the higher the melt viscosity of LCP, the larger the molecular weight of LCP. When the molecular weight of LCP is large, the ratio of the shortcomings of the polymer (LCP molecules) is small. It is believed that due to the influence of the molecular weight of such LCP, the ratio of shortcomings, etc., the LCP fibers (fibrous particles) in the LCP powder manufactured by the method described later from the LCP raw material become long fibers, and the ratio of the powder with a small aspect ratio is reduced, thereby obtaining the effect of increasing the ratio of fibrous particles. Therefore, it is believed that the CTE of the LCP film is reduced and the strength of the LCP film is improved.

[0032] It should be noted that liquid crystal polymer powder having a melt viscosity exceeding 80 Pa·s is difficult to prepare in practice because the viscosity of the original LCP raw material is too high and there is a tendency for a small amount of foreign matter to be generated at the discharge port during granulation.

[0033] The melt viscosity of the liquid crystal polymer powder is more preferably 30 to 70 Pa·s. In this case, the aspect ratio of the fibrous particles constituting the LCP powder is larger (long fibers), and the linear expansion coefficient of the LCP film produced using the LCP powder can be reduced.

[0034] The melt viscosity of the liquid crystal polymer powder was measured under the following measurement conditions in accordance with JIS K7199 using a capilograph manufactured by Toyo Seiki Seisaku-sho, Ltd.

[0035] Temperature: Melting point of liquid crystal polymer + 25°C)

[0036] Shear speed: 1000 sec -1

[0037] Capillary: length 20mm / diameter 1mm

[0038] It should be noted that, although the above-mentioned Patent Document 2 mentions the relationship between the melt viscosity of LCP and the moldability, it does not mention anything about the melt viscosity of LCP and the mechanical properties of LCP molded products.

[0039] The melt viscosity of the liquid crystal polymer powder is 15 to 77 Pa·s or more, and the aspect ratio of the fibrous particles constituting the liquid crystal polymer powder is large (long fiber shape), and the average fiber thickness becomes thinner. Therefore, the physical entanglement between the fibers increases, and the fiber diameter is also thin, so it melts and bonds at a lower temperature. Therefore, it is believed that the strength of the fiber mat is improved even if it is heated below the melting point of the liquid crystal polymer raw material. It is believed that the principle that fibers with finer fiber diameters melt at lower temperatures is that the proportion of the surface in the volume of the finer fibers is greater, resulting in lower crystallinity and therefore melting at a lower temperature. It is believed that since the crystal has a regular structure, there are few parts such as the surface where the bonds are broken and the degree of freedom is increased.

[0040] (fibrous particles)

[0041] The fibrous particles contained in the LCP powder are not particularly limited as long as they contain a fibrous portion. The fibrous portion may be linear or branched.

[0042] The average aspect ratio of the fibrous particles is preferably 10 to 500, more preferably 300 or less, and further preferably 100 or less. The average diameter of the fibrous particles is more preferably 2 μm or less, and more preferably 1 μm or less.

[0043] LCP powder containing such fine fibrous particles cannot be produced by conventionally known methods. For example, the aspect ratio of ultrafine fibers composed of LCP obtained by cutting continuous LCP long fibers produced by conventional electrospinning methods is usually more than 500.

[0044] In addition, the average diameter and average aspect ratio of the fibrous particles contained in the LCP powder were measured by the following method.

[0045] (Measurement of average diameter and average aspect ratio of fibrous particles)

[0046] The LCP powder to be measured is dispersed in ethanol to prepare a slurry containing 0.01% by mass of LCP powder. At this time, the slurry is prepared so that the content of water in the slurry is less than 1% by mass. Then, after 5 to 10 μL of the slurry is dropped onto a glass slide, the slurry on the glass slide is naturally dried. By allowing the slurry to dry naturally, the LCP powder is configured on the glass slide.

[0047] Next, a scanning electron microscope is used to observe a predetermined area of ​​the LCP powder disposed on a glass slide, thereby collecting image data of more than 100 particles constituting the LCP powder. It should be noted that in the collection of image data, the above-mentioned area is set according to the size of each particle of LCP so that the number of image data becomes more than 100. In addition, for each particle of LCP, in order to suppress the omission of image data collection or the generation of measurement errors, the magnification of the scanning electron microscope is appropriately changed to 500 times, 3000 times or 10000 times, and the above-mentioned image data is collected.

[0048] Next, the lengthwise dimension and widthwise dimension of each particle of the LCP powder are measured using the acquired image data.

[0049] The direction of the straight line connecting the two ends of the longest path in the path that can be taken on a particle of the LCP powder captured along each of the above-mentioned image data, that is, the path from one end of the particle through the approximate center of the particle to the end on the opposite side of the one end, is defined as the long side direction. Then, the length of the straight line connecting the two ends of the longest path is measured as the long side direction dimension.

[0050] In addition, the size of the particle in the direction orthogonal to the long side direction is measured at three different locations on the long side direction of one particle of the LCP powder. The average value of the sizes measured at these three locations is taken as the width direction size (fiber diameter) of each particle of the LCP powder.

[0051] Furthermore, the ratio of the length in the long-side direction to the fiber diameter [length in the long-side direction / fiber diameter] was calculated as the aspect ratio of the fibrous particles.

[0052] Then, the average value of the fiber diameters measured for 100 fibrous particles was defined as the average diameter.

[0053] In addition, the average value of the aspect ratios measured for 100 fibrous particles was taken as the average aspect ratio.

[0054] In addition, the fibrous particles may be contained in the LCP powder as aggregates in which the fibrous particles are aggregated.

[0055] In addition, the fibrous particles have a tendency that the axial direction of the LCP molecules constituting the fibrous particles is consistent with the long side direction of the fibrous particles. It should be noted that this is because when the LCP powder is manufactured through the fibrillation step described later, a plurality of structural domains formed by the LCP molecules being bundled are destroyed each other, thereby the axial direction of the LCP molecules is oriented along the long side direction of the fibrous particles.

[0056] The bulk density of LCP powder is preferably 2 to 5 mg / cm 3 , more preferably 2.5 to 4.5 mg / cm 3 , more preferably 2.5 to 4 mg / cm 3 .

[0057] In the LCP powder, the content (number ratio) of particles other than fibrous particles (substantially non-fibrous bulk particles) is preferably 20% or less. For example, when the LCP powder is placed on a plane, particles with a maximum height of 10 μm or less are fibrous particles, and particles with a maximum height greater than 10 μm are bulk particles.

[0058] The value of D50 (average particle size) of the LCP powder measured by particle size measurement using a particle size distribution measuring apparatus using a laser diffraction scattering method is preferably 13 μm or less.

[0059] The melting point of LCP is preferably more than 300°C, and more preferably more than 330°C. The "melting point" mentioned here refers to the "endothermic peak temperature" when the LCP is heated to 400°C in an inert atmosphere, cooled to room temperature at a cooling rate of more than 40°C / minute, and heated again at a heating rate of 40°C / minute while being measured using a differential scanning calorimeter. When the melting point (endothermic peak temperature) of LCP exceeds 300°C, an LCP film with excellent heat resistance can be obtained. Furthermore, when the LCP film is used as a circuit substrate, damage to the circuit substrate during repair using a soldering iron can be suppressed. The melting point of the LCP powder is preferably usually 1 to 3°C lower than the melting point of the liquid crystal polymer raw material.

[0060] In addition, from the viewpoint of forming an LCP film, the melting point of LCP is preferably lower than the decomposition temperature of LCP, and is preferably 400° C. or lower, for example.

[0061] The liquid crystal polymer powder may further contain a zirconium compound. The liquid crystal polymer powder preferably contains 0.001 wt% to 0.1 wt%, and more preferably 0.003 wt% to 0.05 wt% of the zirconium compound relative to the total amount of the liquid crystal polymer powder. The liquid crystal polymer powder contains a trace amount of zirconium compound, and when irradiated with light in the subsequent processing step, the light absorption characteristics of the zirconium compound can improve the light irradiation efficiency.

[0062] The zirconium compound refers to a compound containing a zirconium atom. Examples of the zirconium compound include zirconium acetate, zirconium hydroxide, zirconium oxide, and the like, with zirconium dioxide (zirconium oxide) being preferably used. The zirconium compound contained in the liquid crystal polymer powder is preferably in the form of particles, and the particle size is preferably 1 nm to 500 μm, more preferably 10 nm to 100 nm. It is speculated that the zirconium compound is mixed with a substance used as a medium used for coarsely pulverizing the liquid crystal polymer during the manufacturing process of the liquid crystal polymer powder.

[0063] <Liquid crystal polymer film>

[0064] A liquid crystal polymer (LCP) film according to one embodiment of the present invention includes a liquid crystal polymer.

[0065] The MIT folding times of the LCP film of this embodiment is preferably more than 100 times. The MIT folding times refers to the number of bends required to cut the test film when a test film with a width of 10 mm and a thickness of 25 μm taken from the LCP film is subjected to an MIT folding fatigue test under the conditions of a load of 500 g, a curvature radius of 0.2 mm, a bending angle of 135 degrees, and a speed of 175 cpm.

[0066] Thus, the LCP film having an MIT folding resistance of more than 100 can be appropriately used as a circuit substrate for a substrate for FPC (Flexible Printed Circuit), a vibration plate, an organic semiconductor substrate, an organic EL substrate, a vibration damping plate, etc. That is, from the viewpoint of being applicable to the above-mentioned substrates, the LCP film of the present embodiment preferably has excellent folding resistance.

[0067] The linear expansion coefficient in the plane (XY direction) of the LCP film is preferably 20 ppm / °C or less, more preferably 18 to 20 ppm / °C. The linear expansion coefficient of the LCP film is the linear expansion coefficient in the plane (XY direction) of the LCP film measured by the TMA (thermomechanical analysis) method according to JIS K 7197. The conditions of the TMA method are to increase the temperature from room temperature to 150°C at 10°C / min under a nitrogen atmosphere, the load is 10g, and the sample shape is a long strip (5mm×15mm).

[0068] The thickness of the LCP film is preferably, for example, 5 μm to 250 μm.

[0069] The water absorption of LCP film when immersed in water at normal temperature for 24 hours is preferably below 0.2 mass %. In this way, if the above-mentioned water absorption is below 0.2 mass %, LCP film can be more appropriately used as a circuit substrate component for high frequency. If the LCP film with the above-mentioned water absorption being below 0.2 mass % is used as a circuit substrate component for high frequency, the circuit substrate for high frequency can be suppressed to contain water with extremely high dielectric constant, the increase of dielectric loss caused by the increase of relative dielectric constant and dielectric loss tangent can be suppressed, and then the mismatch of characteristic impedance caused by the change of dielectric constant and the generation of transmission loss brought therewith can be suppressed. It should be noted that, for example, the LCP film composed of the liquid crystal polymer of the structure from amine introduced in the molecular structure is higher because of water absorption, so the water absorption exceeds 0.2 mass %.

[0070] The LCP film of this embodiment can be bonded with copper foil on at least one side, or can be bonded with copper foil on both sides. In this case, the LCP film of this embodiment can be used as a laminated molded body, for example, as FCCL (Flexible Copper Clad Laminates) that can form circuits using a subtractive method.

[0071] <Fiber Felt>

[0072] A fiber mat according to one embodiment of the present invention includes a liquid crystal polymer. The breaking tension of the fiber mat according to this embodiment is preferably 0.8 N / 20 mm or more, more preferably 1.0 N / 20 mm or more. The breaking tension of the fiber mat may be 1.2 N / 20 mm or more, or 1.5 N / 20 mm or more. According to the present invention, even if heat treatment is performed at a temperature below the melting point of the liquid crystal polymer, the breaking tension can be increased compared to the fiber mat before the heat treatment, and a fiber mat having a breaking tension of 1.0 N / 20 mm or more can be obtained.

[0073] The breaking tension of the fiber mat can be measured using an autograph (AG-XDplus manufactured by Shimadzu Corporation). In this case, the width of the fiber mat during the measurement is 20 mm.

[0074] The overall basis weight of the fiber felt is approximately 30-40g / m 2 The overall density of the fiber mat is, for example, 0.30 to 0.60 g / m 3 , as the fusion area of ​​the liquid crystal powder polymer in the thickness direction becomes larger, the density increases.

[0075] The thickness of the fiber mat is approximately 50 to 100 μm, and the thickness decreases as the fusion region of the liquid crystal powder polymer in the thickness direction becomes larger.

[0076] <<Method for producing liquid crystal polymer powder, liquid crystal polymer film and fiber mat>>

[0077] Hereinafter, a method for producing a liquid crystal polymer powder and a liquid crystal polymer film according to one embodiment of the present invention will be described.

[0078] <Method for producing liquid crystal polymer powder>

[0079] like Figure 5 As shown, the method for producing a liquid crystal polymer powder according to the present embodiment includes a coarse pulverization step ( S11 ), a fine pulverization step ( S12 ), a coarse particle removal step ( S13 ), and a fiberization step ( S14 ) in this order.

[0080] (Preparation of LCP Raw Material) In the method for producing a liquid crystal polymer powder according to the present embodiment, first, a raw material (LCP raw material) composed of a liquid crystal polymer is prepared.

[0081] As LCP raw materials, uniaxially oriented granular, biaxially oriented film or powder liquid crystal polymers can be cited. From the viewpoint of manufacturing cost, preferably a granular or powder liquid crystal polymer that is cheaper than a film-like liquid crystal polymer, more preferably a granular liquid crystal polymer. It should be noted that in the present embodiment, the LCP raw material does not include a fibrous liquid crystal polymer that is directly formed by an electrostatic spinning method or a melt-blown method. However, the LCP raw material may include a fibrous liquid crystal polymer that is processed by crushing a granular liquid crystal polymer or a powdery liquid crystal polymer.

[0082] The melt viscosity of the LCP raw material is 15 to 79 Pa·s, preferably 20 to 79 Pa·s. The melt viscosity of the LCP raw material is substantially the same as the melt viscosity of the liquid crystal polymer powder constituting the fibrous particles contained in the LCP powder.

[0083] The melting point of the LCP raw material is preferably higher than 300° C., more preferably higher than 330° C., and further preferably higher than 350° C. Thus, a liquid crystal polymer film having excellent heat resistance and including a liquid crystal polymer having a melting point exceeding 300° C. can be obtained.

[0084] In the case where the melting point of the LCP raw material is higher than 300°C, the LCP raw material is preferably a granular or powdered liquid crystal polymer. Film-like liquid crystal polymers are usually formed using a melt extrusion method. However, when an attempt is made to use a liquid crystal polymer having a melting point higher than 300°C and to form a film-like liquid crystal polymer by a melt extrusion method, a large number of fish eyes of the liquid crystal polymer are generated or deterioration occurs due to decomposition. This is because for a liquid crystal polymer having a melting point higher than 300°C, if a film-like liquid crystal polymer is to be formed by a melt extrusion method, the liquid crystal polymer needs to be heated to a temperature close to the decomposition temperature and continuously kneaded.

[0085] (Coarse pulverization step: S11)

[0086] In the coarse pulverization step, the LCP raw material is coarsely pulverized. For example, the LCP raw material is coarsely pulverized using a shredder. The size of the coarsely pulverized LCP particles is not particularly limited as long as they can be used as a raw material for the fine pulverization step described later. The maximum particle size of the coarsely pulverized LCP particles is, for example, less than 3 mm.

[0087] The method for manufacturing the LCP film in the present embodiment does not necessarily have a coarse pulverization step. For example, as long as the LCP raw material can be used as a raw material for the fine pulverization step, the LCP raw material can be directly used as a raw material for the fine pulverization step. However, when the melting point of the LCP raw material is higher than 330°C, it is preferred to implement the coarse pulverization step before the next fine pulverization step. In the coarse pulverization step, the coarse pulverization is preferably carried out under high-pressure dispersion. The number of dispersion treatments is preferably 1 to 50 times, and more preferably 1 to 10 times. By using high-pressure dispersion for pulverization in the coarse pulverization step, it is easy to obtain a granular finely pulverized liquid crystal polymer in the subsequent step.

[0088] (Fine pulverization step: S12)

[0089] In the fine pulverization step, the LCP raw material (after the coarse pulverization step) is pulverized in a state dispersed in liquid nitrogen to obtain a granular finely pulverized liquid crystal polymer (finely pulverized LCP).

[0090] In the fine pulverizing step, it is preferred to use a medium to pulverize the LCP raw material dispersed in liquid nitrogen. The medium is, for example, beads. As the medium, for example, particles of zirconium oxide can be used. The particle size of the zirconium oxide used as the medium is preferably 0.1 mm to 10 mm, and more preferably 1 mm to 8 mm. In the fine pulverizing step of the present embodiment, from the perspective of handling liquid nitrogen, it is preferred to use a bead mill with fewer technical problems. As an apparatus that can be used in the fine pulverizing step, for example, the liquid nitrogen bead mill "LNM-08" manufactured by IMEX Corporation can be cited.

[0091] In the fine pulverizing step of the present embodiment, the pulverizing method of pulverizing the liquid crystal polymer in a state of being dispersed in liquid nitrogen is different from the conventional freezing pulverizing method. The conventional freezing pulverizing method is a method of pulverizing the pulverized raw material while injecting liquid nitrogen into the pulverizing raw material and the pulverizing device body, but most of the liquid nitrogen is gasified when the pulverized raw material is pulverized. That is, in the conventional freezing pulverizing method, most of the pulverized raw material is not dispersed in the liquid nitrogen when the pulverized raw material is pulverized.

[0092] In the existing freezing and pulverizing method, the heat of the pulverized raw material itself, the heat generated from the pulverizing device, and the heat generated by the pulverization of the pulverized raw material cause the liquid nitrogen to vaporize in a very short time. Therefore, in the existing freezing and pulverizing method, the raw material being pulverized inside the pulverizing device becomes a temperature far higher than -196°C, which is the boiling point of liquid nitrogen. That is, in the existing freezing and pulverizing method, pulverization is carried out under the condition that the temperature inside the pulverizing device is usually around -100°C to 0°C. In the existing freezing and pulverizing method, even if liquid nitrogen is supplied as much as possible, the temperature inside the pulverizing device is about -150°C at the lowest.

[0093] Therefore, in the conventional freeze-crushing method, for example, when a uniaxially oriented particulate liquid crystal polymer (or its coarsely pulverized product) is pulverized, the pulverization is performed along a plane substantially parallel to the axial direction of the molecular axis of the liquid crystal polymer, and therefore, it is believed that a fibrous liquid crystal polymer having a very large aspect ratio and a fiber diameter much larger than 3 μm is obtained. That is, in the conventional freeze-crushing method, even if a uniaxially oriented particulate liquid crystal polymer is pulverized, a granular finely pulverized liquid crystal polymer such as that used in the present embodiment cannot be obtained.

[0094] In the present embodiment, since the raw material to be crushed is crushed in a state where it is dispersed in liquid nitrogen, the raw material is crushed in a further cooled state compared to the existing freeze-crushing method. Specifically, the raw material to be crushed is crushed at a temperature lower than -196°C, which is the boiling point of liquid nitrogen. If the raw material to be crushed at a temperature lower than -196°C is crushed, the raw material is crushed by repeatedly performing brittle failure of the raw material to be crushed. Thus, for example, even when a uniaxially oriented liquid crystal polymer is crushed, it is not only broken on a surface roughly parallel to the axial direction of the molecular axis of the liquid crystal polymer, but also brittlely broken along a surface intersecting the above-mentioned axial direction, so that a granular finely crushed LCP can be obtained.

[0095] In the freeze-crushing method of this embodiment, the rotation speed of freeze-crushing is preferably 1800 rpm or more, more preferably 2000 rpm or more, and further preferably 2500 rpm or more. By adopting such a rotation speed, it is easy to obtain a granular finely crushed liquid crystal polymer having a desired aspect ratio.

[0096] In the fine pulverization step of the present embodiment, the liquid crystal polymer that has become granular by brittle fracture is continuously impacted in a brittle state by a medium, etc. Thus, a plurality of fine cracks are formed from the outer surface to the inside of the liquid crystal polymer obtained in the fine pulverization step of the present embodiment.

[0097] The finely pulverized LCP particles obtained in the fine pulverization step preferably have a D50 of 50 μm or less as measured by a particle size distribution measuring device using a laser diffraction scattering method. This can prevent the finely pulverized LCP particles from clogging the nozzle in the fiberizing step described below.

[0098] (Coarse Particle Removal Step: S13)

[0099] Next, in the coarse particle removal step, coarse particles are removed from the granular finely pulverized LCP obtained in the above-mentioned finely pulverized step. For example, by sieving the granular finely pulverized LCP on a sieve to obtain the granular finely pulverized LCP under the sieve, and removing the granular liquid crystal polymer on the sieve, the coarse particles contained in the granular finely pulverized LCP can be removed. The type of sieve can be appropriately selected, and as the sieve, for example, a sieve with a mesh size of 53 μm can be cited. It should be noted that the method for producing the liquid crystal polymer powder of this embodiment does not necessarily have to include a coarse particle removal step.

[0100] (Fibration process: S14)

[0101] Next, in the fiberizing process, the granular liquid crystal polymer is crushed by a wet high-pressure crushing device to obtain a liquid crystal polymer powder. In the fiberizing process, the finely pulverized LCP is first dispersed in a dispersion medium for the fiberizing process. The dispersed finely pulverized LCP may not be free of coarse particles, but preferably free of coarse particles. As the dispersion medium for the fiberizing process, for example, water, ethanol, methanol, isopropanol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane or a mixture thereof can be cited.

[0102] Then, the finely pulverized LCP in the state of being dispersed in the dispersion medium for the fiberization process, that is, the finely pulverized LCP in a paste or slurry state, is passed through the nozzle under a high-pressure pressurized state. By passing the nozzle at high pressure, the shear force or collision energy brought by the high-speed flow in the nozzle acts on the liquid crystal polymer, and the granular finely pulverized LCP is crushed, thereby performing the fiberization of the liquid crystal polymer, and a liquid crystal polymer powder that can be used in the method for manufacturing a liquid crystal polymer film can be obtained. From the viewpoint of applying high shear force or high collision energy, it is preferred to reduce the nozzle diameter of the above-mentioned nozzle as much as possible within a range where the clogging of the finely pulverized LCP does not occur in the above-mentioned nozzle. The particle size of the granular finely pulverized LCP in the present embodiment is relatively small, so the nozzle diameter of the wet high-pressure crushing device used in the fiberization process can be reduced. The nozzle diameter is, for example, less than 0.2 mm.

[0103] In the present embodiment, as described above, a plurality of fine cracks are formed in the granular finely pulverized LCP powder. Therefore, by pressurization in the wet high-pressure crushing device, the dispersion medium invades the interior of the finely pulverized LCP from the fine cracks. Then, when the paste-like or slurry-like finely pulverized LCP passes through the nozzle and is located under normal pressure, the dispersion medium invading the interior of the finely pulverized LCP expands in a very short time. By the expansion of the dispersion medium invading the interior of the finely pulverized LCP, the finely pulverized LCP is destroyed from the interior. Therefore, fiberization proceeds to the interior of the finely pulverized LCP, and the molecules of the liquid crystal polymer are separated into structural domain units arranged in a unidirectional manner. In this way, in the fiberization process in the present embodiment, by defibrillating the granular finely pulverized LCP obtained in the finely pulverized process in the present embodiment, a liquid crystal polymer powder having a low content of blocky particles and fine fibrous shape can be obtained compared to a liquid crystal polymer powder obtained by crushing a granular liquid crystal polymer obtained in an existing freeze-pulverizing method.

[0104] In the fiberizing step in the present embodiment, the liquid crystal polymer powder can be obtained by crushing the finely pulverized LCP multiple times using a wet high-pressure crushing device.

[0105] <Method for producing liquid crystal polymer film>

[0106] like Figure 6 As shown, the method for producing a liquid crystal polymer film according to the present embodiment includes a dispersion step ( S21 ), a felting step ( S22 ), a heat pressing step ( S23 ), and a metal foil removing step ( S24 ).

[0107] (Dispersion process: S21)

[0108] In the dispersion step, which is the first step of the method for producing a liquid crystal polymer film, the liquid crystal polymer powder is dispersed in a dispersion medium to form a paste or slurry. Thus, in this embodiment, since the fine fibrous liquid crystal polymer powder is used, the liquid crystal polymer powder can be dispersed in a high-viscosity dispersion medium. Thus, a homogeneous liquid crystal polymer film can be produced.

[0109] As the dispersion medium used in the dispersion process, water, terpineol or ethanol and mixtures thereof can be cited. For example, when terpineol is used as the dispersion medium, a liquid crystal polymer powder in a paste state is obtained. When a mixture of ethanol and water is used as the dispersion medium, a liquid crystal polymer in a slurry state is obtained.

[0110] (Felting process: S22)

[0111] Next, in the felting step, the liquid crystal polymer powder in a paste or slurry state is dried to form a liquid crystal polymer fiber mat. In one embodiment of the present invention, the felting step includes, for example, a coating step and a drying step.

[0112] In the coating process, the liquid crystal polymer powder in a paste state is coated on a metal foil such as copper foil. In the coating process, the liquid crystal polymer powder in a paste state is coated on a metal foil such as copper foil as described above, but a polyimide film, a PTFE (polytetrafluoroethylene) film, or a composite sheet composed of a reinforcing material such as glass fiber fabric and a heat-resistant resin may be used instead of the metal foil. This makes it easy to produce liquid crystal polymer films industrially.

[0113] Next, the liquid crystal polymer paste applied to the copper foil is heated and dried in a drying process to vaporize the dispersion medium. The dispersion medium can be vaporized by suction. By the above heating and drying, a liquid crystal polymer fiber mat is formed on a metal foil such as a copper foil.

[0114] In addition, in the drying process, since the dispersion medium is slowly removed from the liquid crystal polymer paste powder, the overall thickness of the liquid crystal polymer paste powder gradually becomes thinner during drying. Therefore, the thickness of the liquid crystal polymer fiber felt is thinner than the overall thickness of the liquid crystal polymer paste formed on the copper foil. Specifically, in this embodiment, the overall thickness of the liquid crystal polymer paste powder is about 700 μm, and the thickness of the liquid crystal polymer fiber felt is, for example, about 150 μm.

[0115] Furthermore, as the overall thickness of the paste-like LCP powder gradually becomes thinner during drying, the orientation of the long side direction of the fibrous particles in the LCP powder changes. Specifically, among the fibrous particles, the fibrous particles having a long side direction along the overall thickness direction of the paste-like liquid crystal polymer powder are inclined so that the long side direction is oriented in the in-plane direction of the copper foil. Therefore, the long side direction of the fibrous particles in the formed liquid crystal polymer fiber mat is anisotropic.

[0116] In the felting process, a liquid crystal polymer paste is further applied to the liquid crystal polymer fiber felt formed on the metal foil in the drying process, and then dried, thereby gasifying the dispersion medium. In this way, the felting process may include a coating process and a drying process, which are repeated in sequence. In this way, a liquid crystal polymer fiber felt having a desired weight per unit area can be obtained.

[0117] It should be noted that the liquid crystal polymer fiber mat in the present embodiment is formed by fibrous particles of liquid crystal polymer powder being entangled with each other. In addition, the liquid crystal polymer fiber mat has gaps between the liquid crystal polymer powders. As described above, the long side direction of the fibrous particles in the liquid crystal polymer powder is generally inclined toward the in-plane direction of the copper foil, so the void ratio of the liquid crystal polymer fiber mat tends to be larger than that of the liquid crystal polymer felt obtained by felting the existing liquid crystal polymer powder without fibrous particles. The void ratio is, for example, 80% to 90%.

[0118] The felting process in the present embodiment can replace the above-mentioned coating process and drying process, and the pasty or slurry-like liquid crystal polymer powder can be formed into a liquid crystal polymer fiber felt by a papermaking method. According to the above-mentioned papermaking method, the special dispersion medium (such as expensive pine alcohol) used in the above-mentioned coating process can be omitted. In addition, in the papermaking method, the dispersion medium used in the dispersion process can be recovered for reuse. In this way, the liquid crystal polymer film can be manufactured cheaply by the above-mentioned papermaking method.

[0119] In the felting process using the papermaking method, specifically, first, a paste or slurry-like liquid crystal polymer powder is scooped up on a mesh, a non-woven microporous sheet or a fabric, and then the paste or slurry-like liquid crystal polymer disposed on the mesh is heated and dried to obtain a liquid crystal polymer fiber felt.

[0120] (Hot pressing process: S23)

[0121] Next, in a hot pressing process, a liquid crystal polymer film is obtained by hot pressing the liquid crystal polymer fiber felt. Specifically, in the hot pressing process, the liquid crystal polymer fiber felt is hot pressed together with the copper foil. Thus, the hot pressing process also serves as a process for bonding the liquid crystal polymer film and the copper foil to each other, so that a liquid crystal polymer film bonded with the copper foil can be obtained at a low price. It should be noted that in the hot pressing process, when heating for a long time, it is preferred to perform vacuum hot pressing on the liquid crystal polymer fiber felt. In addition, in the hot pressing process, before performing vacuum hot pressing, pre-pressing can be performed at a temperature below 220°C. By performing pre-pressing, the density of the fiber felt can be increased and the linear expansion coefficient (CTE) of the liquid crystal polymer film can be reduced. The density of the fiber felt is preferably 0.1 to 1.5 g / cm 3 , more preferably 0.3 to 1.4 g / cm 3 .

[0122] In the hot pressing step, the hot pressing is preferably performed at a temperature about 5°C to 15°C lower than the melting point of the liquid crystal polymer constituting the liquid crystal polymer powder. If the hot pressing is performed at a temperature about 5°C to 15°C lower than the endothermic peak temperature, the liquid crystal polymers are easily sintered.

[0123] In the hot pressing step, a polyimide film, a PTFE film, or a composite sheet composed of a reinforcing material such as glass fiber fabric and a heat-resistant resin may be sandwiched between the punch used in the hot pressing step and the liquid crystal polymer fiber mat as a release film.

[0124] In addition, an additional copper foil can be sandwiched between the punch and the liquid crystal polymer fiber mat instead of the polyimide film. In this case, a liquid crystal polymer film with copper foil bonded on both sides can be obtained. The liquid crystal polymer film with copper foil bonded on both sides can be used as a double-sided copper-clad FCCL.

[0125] The outer dimensions of the liquid crystal polymer film formed by the hot pressing process observed from the thickness direction, that is, the plane dimensions along the film surface, are roughly the same as those of the liquid crystal polymer fiber felt before hot pressing. Moreover, by hot pressing, the fibrous particles of the liquid crystal polymer powder in the liquid crystal polymer fiber felt, which have a long side direction along the thickness direction of the liquid crystal polymer fiber felt, are heated while being pushed in the in-plane direction of the copper foil. Since the liquid crystal polymer constituting the liquid crystal polymer powder has an axial direction of the molecules in the long side direction of the fibrous particles, the axial direction of the molecules of the liquid crystal polymer is also pushed in the in-plane direction of the copper foil. Therefore, except for the molecules constituting the blocky particles, the axial directions of the molecules constituting the liquid crystal polymer are oriented in the in-plane direction of the liquid crystal polymer film in the thickness direction of the liquid crystal polymer film. Therefore, in the formed liquid crystal polymer film, there is a tendency that the main orientation direction of the molecules of the liquid crystal polymer is along the in-plane direction of the copper foil, that is, the in-plane direction of the liquid crystal polymer film.

[0126] Therefore, it is considered that the in-plane linear expansion coefficient of the liquid crystal polymer film of the present embodiment is reduced. In addition, a liquid crystal polymer film having a low in-plane linear expansion coefficient has an advantage of excellent dimensional stability.

[0127] In addition, when copper foil is bonded to a liquid crystal polymer film, the linear expansion coefficient of the liquid crystal polymer film can be reduced to the same level as the linear expansion coefficient of copper foil (about 18 to 20 ppm / °C). As a result, in the liquid crystal polymer film bonded with copper foil, defects such as warping due to thermal shrinkage can be suppressed.

[0128] Furthermore, the liquid crystal polymer powder in the liquid crystal polymer fiber felt is sometimes bonded to each other in a state where the fibrous particles are entangled with each other. Thus, the liquid crystal polymer in the liquid crystal polymer film has a structure in which the molecules are entangled with each other. In addition, since the above-mentioned fibrous particles have a larger surface area than the spherical liquid crystal polymer having the same volume, the bonding area when the liquid crystal polymer powders are bonded to each other is also increased by the hot pressing process. Thus, the toughness and folding strength of the liquid crystal polymer film of this embodiment are improved. In addition, by the hot pressing process, the thickness of the liquid crystal polymer film becomes thinner than that of the liquid crystal polymer fiber felt.

[0129] It should be noted that the liquid crystal polymer felt obtained by felting the conventional liquid crystal polymer powder that does not contain the fibrous particles as described above does not contain fibrous particles having axial directions of the molecular axes in the long-side direction. Therefore, even if such a liquid crystal polymer felt is heat-pressed, the axial directions of the molecules constituting the liquid crystal polymer in the liquid crystal polymer film are not pushed down. Therefore, even if a liquid crystal polymer film is manufactured using the conventional liquid crystal polymer powder that does not contain fibrous particles, the main orientation directions of the molecules constituting the liquid crystal polymer are not along the in-plane direction of the liquid crystal polymer film.

[0130] In addition, even if the liquid crystal polymer fiber felt obtained by felting the existing liquid crystal polymer powder that does not contain the above-mentioned fibrous particles is hot-pressed, the bonding area when the liquid crystal polymer powders are bonded to each other is extremely small. Therefore, when the liquid crystal polymer film manufactured using the existing liquid crystal polymer powder that does not contain fibrous particles is subjected to external force, the stress is concentrated on the bonding portion between the liquid crystal polymer powders. Moreover, since the bonding area of ​​the bonding portion is small, the liquid crystal polymer film is destroyed at the bonding portion when subjected to external force. In this way, the strength of the liquid crystal polymer film manufactured using the existing liquid crystal polymer powder that does not contain fibrous particles is weak, and the toughness and folding strength become low. This liquid crystal polymer film cannot be used as a substrate, vibration plate or vibration damping plate for FPC.

[0131] (Metal foil removal step: S24)

[0132] Finally, if necessary, the metal foil bonded to the liquid crystal polymer film may be removed by etching, etc. Thus, a single liquid crystal polymer film to which the metal foil is not bonded can be obtained.

[0133] According to the method for manufacturing a liquid crystal polymer film of this embodiment, a liquid crystal polymer film is manufactured by using a liquid crystal polymer powder containing fibrous particles with an average aspect ratio of 10 to 500 and an average diameter of 2 μm or less, which was not possible before, thereby obtaining a liquid crystal polymer film having excellent folding strength and other properties suitable for use as a circuit substrate.

[0134] It should be noted that in the past, LCP films were made by melt extrusion, solution casting, etc. In these methods, it is necessary to use an LCP with a low melting point (LCP with an amide bond, etc.) that can be melted in a manufacturing device. In contrast, in the method for manufacturing the LCP film of the present embodiment, it is not necessary to melt the LCP, so an LCP with a high melting point as described above can be used. Therefore, for example, a liquid crystal polymer having a melting point exceeding 330°C can be used, and a liquid crystal polymer film having excellent heat resistance containing such a liquid crystal polymer having a melting point exceeding 330°C can be manufactured.

[0135] <Manufacturing method of fiber felt>

[0136] like Figure 7 As shown, the fiber mat production method of the present embodiment includes a dispersing step (S31) and a felting step (S32). The dispersing step (S31) is the same as the dispersing step (S21) of the liquid crystal polymer film production method.

[0137] The felting step (S32) forms the slurry-like liquid crystal polymer powder into a liquid crystal polymer fiber felt by a papermaking method. In the papermaking method, the dispersion medium used in the dispersion step can be recovered and reused, and the fiber felt can be produced at a low cost.

[0138] Figure 8 1 is a diagram showing an example of a felting step of felting a liquid crystal polymer powder in a fiber mat production process. Figure 8 The felting process will be described in detail.

[0139] like Figure 8 As shown, a paper machine 100 is used in the felting process. The paper machine 100 includes: a supply roller 15 for supplying the microporous sheet 10, a winding roller (not shown) for collecting the microporous sheet 10, a papermaking net 20, conveying rollers 25 and 26, a storage unit 40 for storing a dispersion medium 41 in which the liquid crystal polymer powder is dispersed, a heating device 50, and a light irradiation device 60.

[0140] The papermaking net 20 is, for example, a papermaking net of about 80 to 100 meshes. That is, the papermaking net 20 has a pore size of about 150 μm to 180 μm. The papermaking net 20 is transported by transport rollers 25 and 26 arranged in the transport direction. The transport roller 26 is arranged on the downstream side of the transport roller 26. The papermaking net 20 is transported by these transport rollers 25 and 26 and passes through the storage unit 40.

[0141] The supply roller 15 supplies the microporous sheet 10 onto the papermaking wire 20. The microporous sheet 10 functions as a support for the liquid crystal polymer powder. The microporous sheet 10 disposed on the papermaking wire 20 is conveyed by the papermaking wire 20 and passes through the storage unit 40. The microporous sheet 10 passing through the storage unit 40 is peeled off from the papermaking wire 20 and wound up by the winding roller.

[0142] The microporous sheet 10 has finer mesh than the papermaking net 20. The microporous sheet 10 is preferably about 157 mesh or larger. That is, the microporous sheet 10 preferably has a pore size of about 100 μm or less. This allows the capture of fine liquid crystal polymer powder dispersed in the dispersion medium.

[0143] More preferably, the microporous sheet 10 preferably has a pore size of about 5 μm to 50 μm. If the pore size of the microporous sheet 10 is too small, the water filterability deteriorates and the time required for dehydration becomes longer. On the other hand, if the pore size of the microporous sheet 10 is too large, it is difficult to capture fine fibers (fine liquid crystal polymer powder) and the yield rate deteriorates.

[0144] When a microporous sheet 10 with a pore size deviation is selected, the texture of the formed fiber mat is affected, so when a high uniformity is required for the fiber mat, a net woven into a mesh shape periodically is preferably used. That is, as the microporous sheet 10, a net with a uniform pore size and no deviation in the position of the pores is preferably used.

[0145] As the microporous sheet 10, for example, a woven mesh having a pore size of 50 μm or less can be used. As the woven mesh, for example, a mesh made of synthetic fibers such as polyester can be used.

[0146] In addition, as the microporous sheet 10, for example, a sheet having a weight per unit area of ​​15 g / m 2 The following wet nonwoven fabric. As the wet nonwoven fabric, a nonwoven fabric composed of microfibers can be used. The microfibers are composed of synthetic fibers such as polyester.

[0147] The heating device 50 is disposed downstream of the storage unit 40 in the conveying direction. The heating device 50 heats and dries the liquid crystal polymer powder 30 picked up to the microporous sheet 10 . Thus, a fiber mat is formed on the microporous sheet 10 .

[0148] The light irradiation device 60 is disposed downstream of the heating device 50 in the conveying direction. The light irradiation device 60 irradiates light to the fiber mat formed on the microporous sheet 10. The light irradiation device 60 can be a flash lamp, for example.

[0149] The light irradiation device 60 preferably irradiates pulsed light. Since the pulsed light is absorbed by the surface of the fiber felt (the first main surface 31), the support body (microporous sheet 10) supporting the fiber felt will not deteriorate due to light irradiation. Therefore, even a material with a lower melting point than the fiber felt can be used as a support body, and the range of choices for the support body is expanded. In addition, since the fiber felt can be prevented from fusing to the support body, the support body can be reused. As the light irradiation device 60, a light irradiation device (PulseForge (registered trademark) 1300 manufactured by NovaCentrix) can be used.

[0150] The felting step (S32) includes a picking-up step, a peeling step, a drying step, and may further include a light irradiation step. In the felting step (S32), first, the dispersed liquid crystal polymer powder is picked up to the microporous sheet 10 by the picking-up step. Specifically, the microporous sheet 10 supplied to the papermaking net 20 is conveyed by the papermaking net 20 and passed through the storage unit 40. At this time, the liquid crystal polymer powder dispersed in the dispersion medium 41 stored in the storage unit 40 is picked up to the microporous sheet 10.

[0151] Next, in the peeling step, the microporous sheet having the dispersed liquid crystal polymer powder is peeled from the papermaking web 20. Specifically, the microporous sheet 10 is wound up by a winding roll, and the microporous sheet 10 is transported in a direction different from that of the papermaking web 20. It should be noted that the papermaking web 20 may be transported in a direction different from that of the microporous sheet 10 by the transport roll 26.

[0152] Next, in the drying step, the liquid crystal polymer powder picked up to the microporous sheet 10 is heated and dried by the heating device 50 . Thus, the fiber mat 30 composed of the liquid crystal polymer is formed on the microporous sheet 10 .

[0153] Next, in the light irradiation step, the first main surface 31 of the fiber mat 30 located on the side opposite to the side where the microporous sheet 10 is located is irradiated with light. As a result, the liquid crystal polymer powder located on the side of the first main surface 31 is fused. As a result, the strength of the fiber mat 30 is improved, and the fiber mat 30 can be transported to the next step without being damaged.

[0154] Furthermore, since only the liquid crystal polymer powder on the surface layer located on the first main surface 31 side is fused, the density of the fiber mat 30 as a whole is low. Thus, high air permeability and high collection efficiency can be ensured.

[0155] The fiber mat 30 after the light irradiation is arranged on the microporous sheet 10 and is wound up by the winding roller in the winding step.

[0156] Fig. 9 FIG. 2 is a diagram showing a process of irradiating light to the second surface of the fiber mat. Fig. 9 As shown in FIG. 1 , the felting step may further include the following step: peeling the fiber mat 30 on which the first main surface 31 is irradiated with light from the microporous sheet 10, and irradiating the second main surface 32 of the fiber mat 30 on the opposite side to the first main surface 31 with light. In this step, the fine fibers on the second main surface 32 side are fused by irradiating light from a light irradiation device 61. As the light irradiation device 61, the same light irradiation device as the above-mentioned light irradiation device 60 can be used. When irradiating light, the fiber mat 30 is irradiated while being transported.

[0157] When the liquid crystal polymer powder is fused on both sides of the first main surface 31 and the second main surface 32 , the strength of the fiber mat 30 can be further increased.

[0158] In addition, when the fiber mat 30 is peeled off from the microporous sheet 10, the liquid crystal polymer powder is fused on the first main surface 31 side, and the fiber mat 30 has sufficient strength, so it can be peeled off without damaging the fiber mat 30. The fiber mat 30 manufactured in this way can be used directly, and can also be provided to the hot pressing step S23 of the method for manufacturing a liquid crystal polymer film.

[0159] In this embodiment, light is irradiated to the fiber mat 30. When the liquid crystal polymer powder contained in the fiber mat contains a zirconium compound, the light irradiation efficiency may be improved due to the light absorption characteristics of the zirconium compound. By improving the light irradiation efficiency, the breaking tension of the fiber mat may be increased.

[0160] <<Processing method of liquid crystal polymer film and fiber mat>>

[0161] In this embodiment, the liquid crystal polymer film and the fiber mat are subjected to laser irradiation to form through holes or cut portions. Laser irradiation can be performed by, for example, using CO 2 , semiconductor as a laser oscillator. By changing the lens of the laser processing machine, the beam spot diameter of the laser can be changed. In order to perform fine processing, it is preferred that the beam spot diameter is small.

[0162] When the liquid crystal polymer film or the fiber mat contains a zirconium compound, the irradiation efficiency of laser irradiation is improved, and the formation of through holes becomes easy.

[0163] Example

[0164] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these.

[0165] <Example 1>

[0166] (Manufacturing of Liquid Crystal Polymer Powder)

[0167] In Example 1, first, uniaxially oriented liquid crystal polymer particles (cylindrical particles with a diameter of 3 to 4 mm, melting point: 315°C, melt viscosity (MV): 17 Pa·s) are prepared as LCP raw materials. The material of the liquid crystal polymer is a block copolymer of p-hydroxybenzoic acid and 4,6-hydroxynaphthoic acid. It should be noted that the melt viscosity of the liquid crystal polymer (LCP raw material) can be adjusted by the polymerization temperature and polymerization time during the polymerization of the copolymer.

[0168] The LCP raw material was coarsely pulverized by a cutter mill (MF10 manufactured by IKA) and the coarsely pulverized liquid crystal polymer was passed through a 3 mm diameter mesh provided at the discharge port of the cutter mill to obtain a coarsely pulverized liquid crystal polymer.

[0169] Next, the coarsely pulverized liquid crystal polymer was finely pulverized using a liquid nitrogen bead mill (LNM-08 manufactured by IMEX, container capacity: 0.8 L). Specifically, 400 mL of the medium and 30 g of the coarsely pulverized liquid crystal polymer were placed in a container and pulverized at a speed of 2000 rpm for 120 minutes. Zirconium oxide (ZrO 2) beads. It should be noted that in the liquid nitrogen bead mill, the coarsely pulverized liquid crystal polymer is dispersed in liquid nitrogen and wet pulverized. In this way, the coarsely pulverized liquid crystal polymer is pulverized by the liquid nitrogen bead mill to obtain granular finely pulverized LCP.

[0170] The particle size of the finely pulverized LCP was measured. In the particle size measurement, the finely pulverized LCP dispersed in the dispersion medium was subjected to an ultrasonic treatment for 10 seconds, and then placed in a particle size distribution measuring device based on a laser diffraction scattering method (manufactured by Horiba, Ltd., LA-950) for particle size measurement. It should be noted that Ekinen (registered trademark, Japan Alcohol Sales Co., Ltd.), which is a mixed solvent with ethanol as the main agent, was used as the dispersion medium. The measured value of D50 of the finely pulverized LCP was 23 μm.

[0171] Next, the dispersion obtained by dispersing the finely pulverized LCP in the Ekinen was sieved with a 100 μm mesh to remove coarse particles contained in the finely pulverized LCP, and the finely pulverized LCP that passed through the sieve was recovered. The yield of the finely pulverized LCP obtained by removing the coarse particles was 85% by mass.

[0172] Next, the finely pulverized LCP having removed the coarse particles is dispersed in 20% by mass ethanol aqueous solution. Using a wet high-pressure crushing device, the ethanol slurry dispersed with the finely pulverized LCP is repeatedly crushed 5 times under the conditions of a nozzle diameter of 0.2mm and a pressure of 200MPa and is subjected to fibrillation. As a wet high-pressure crushing device, a high-pressure disperser (Nanovar made by Yoshida Machinery Industrial Co., Ltd.) is used. Thus, the liquid crystal polymer powder of the state of being dispersed in the ethanol aqueous solution is obtained.

[0173] (Determination of melt viscosity of liquid crystal polymer powder)

[0174] The liquid crystal polymer powder dispersed in the ethanol aqueous solution was recovered on the filter paper using a suction filtration device. The recovered liquid crystal polymer powder was transferred to an evaporating dish and evaporated to dryness using a hot plate to obtain a dry liquid crystal polymer powder. The drying temperature was 80°C. The melt viscosity of the obtained dry liquid crystal polymer powder was measured.

[0175] The melt viscosity of the liquid crystal polymer powder was measured under the following measurement conditions in accordance with JIS K7199 using a capilograph manufactured by Toyo Seiki Seisaku-sho, Ltd.

[0176] Temperature: 340℃

[0177] Shear speed: 1000Sec-1

[0178] Capillary: length 20mm / diameter 1mm

[0179] At this time, the melt viscosity of the liquid crystal polymer powder was measured to be 15 Pa·s.

[0180] (Manufacture of Liquid Crystal Polymer Film)

[0181] First, a liquid crystal polymer mesh (liquid crystal polymer fiber mat) is formed on the copper foil by applying the liquid crystal polymer powder paste on the copper foil and drying it.

[0182] Specifically, first, 20 times the mass of the dispersed liquid crystal polymer powder is added to the ethanol aqueous solution in which the liquid crystal polymer powder is dispersed. Then, the aqueous solution is heated while stirring, so that water and ethanol are gasified and removed. Thus, the liquid crystal polymer powder dispersed in the pine alcohol is obtained. That is, the liquid crystal polymer powder is dispersed in the pine alcohol as a dispersion medium and made into a paste.

[0183] Next, the liquid crystal polymer paste was applied to the roughened surface of an electrolytic copper foil (Furukawa Electric Co., Ltd., FWJ-WS-12) with a thickness of 12 μm. Then, the electrolytic copper foil coated with the liquid crystal polymer paste was heated to 130°C on a hot plate to vaporize the pine alcohol as a dispersion medium, and the liquid crystal polymer paste on the electrolytic copper foil was dried. In this way, a thin liquid crystal polymer fiber mat was formed on the electrolytic copper foil.

[0184] The above-mentioned paste-like liquid crystal polymer powder is further applied to the thin liquid crystal polymer fiber mat. The applied paste-like liquid crystal polymer powder is dried in the same manner as the previously applied paste-like liquid crystal polymer. In this way, the above-mentioned coating and drying are repeated several times to form a layer of electrolytic copper foil with a unit area weight of 35 g / m 2 Liquid crystal polymer fiber felt.

[0185] Next, the liquid crystal polymer fiber felt formed on the electrolytic copper foil is hot pressed together with the electrolytic copper foil using a vacuum high temperature pressing device (manufactured by Kitagawa Seiki Co., Ltd., KVHC). Specifically, first, a release film is stacked on the side of the liquid crystal polymer fiber felt formed on the electrolytic copper foil opposite to the electrolytic copper foil side. As the release film, a polyimide film (manufactured by DU PONT-TORAY, Kapton (registered trademark) 100H) is used. Then, the liquid crystal polymer fiber felt stacked with the release film is set at room temperature in a vacuum hot pressing device. The set liquid crystal polymer fiber felt is pressed together with the release film and the electrolytic copper foil at a pressing pressure of 0.2MPa, and the temperature is raised to 305°C at a rate of 7°C / min. After reaching 305°C, the temperature is maintained at 305°C, and the liquid crystal polymer film is pressed together with the release film and the electrolytic copper foil at a pressing pressure of 6Mpa for 5 minutes. It should be noted that the size of the extrusion part used in the pressing machine is 170mm square. After the hot pressing was completed, the release film was removed to obtain a liquid crystal polymer film formed on the electrolytic copper foil.

[0186] Finally, the electrolytic copper foil bonded to the liquid crystal polymer film was etched and removed using an aqueous solution of ferric chloride, thereby obtaining a liquid crystal polymer film having a thickness of 25 μm.

[0187] <Examples 2 to 9 and Comparative Example 1>

[0188] In Examples 2 to 9 and Comparative Example 1, LCP particles having melt viscosities of 23, 32, 35, 40, 47, 54, 63, 79, and 14 were used as raw materials (see Table 1). It should be noted that the melt viscosity of the liquid crystal polymer powder is changed by changing at least one of the polymerization temperature and the polymerization time during polymerization. The other points were carried out in the same manner as in Example 1 to produce a liquid crystal polymer powder and obtain a liquid crystal polymer film. It should be noted that the melt viscosities of the produced liquid crystal polymer powders were 20, 29, 33, 36, 45, 50, 60, and 77, respectively.

[0189] [Observation of Liquid Crystal Polymer Powder]

[0190] Figure 1 (a) to (j) are photographs (scanning electron microscope images) of the liquid crystal polymer powders in Comparative Example 1 (MV=12), Example 1 (MV=15), Example 2 (MV=20), Example 3 (MV=29), Example 4 (MV=33), Example 5 (MV=36), Example 6 (MV=45), Example 7 (MV=50), Example 8 (MV=60) and Example 9 (MV=77). Figure 1As can be seen from the photograph, the liquid crystal polymer powder of the example includes thin and long (small fiber diameter and large aspect ratio) fibrous particles compared to the liquid crystal polymer powder of the comparative example.

[0191] [Measurement of Bulk Density of Liquid Crystal Polymer Powder]

[0192] The bulk density of each of the liquid crystal polymer powders of Examples 1 to 9 and Comparative Example 1 was measured.

[0193] Specifically, a dispersion (solid content concentration: 0.1% by mass) was prepared by dispersing the liquid crystal polymer powder in a dispersion medium (20% by mass ethanol solution). The dispersion was fully stirred and then allowed to stand in a measuring cylinder for more than 2 hours. The volume of the portion of the liquid crystal polymer powder in the sedimentation state was read from the scale of the measuring cylinder. The bulk density (mass / volume) was calculated from the measured value of the volume and the mass of the liquid crystal polymer powder (the amount in the dispersion).

[0194] The results of measuring the bulk density of the liquid crystal polymer powder are shown in Tables 1 and Figure 2 .

[0195] [MIT folding fatigue test]

[0196] The liquid crystal polymer films of Examples 1 to 9 and Comparative Example 1 were subjected to MIT folding fatigue tests using an MIT folding fatigue tester. The above test was conducted on a test film with a width of 10 mm and a thickness of 25 μm taken from each liquid crystal polymer film under the conditions of a load of 500 g, a curvature radius of 0.2 mm, a bending angle of 135 degrees, and a speed of 175 cpm. The results of the measurement of the MIT folding times of the liquid crystal polymer films are shown in Tables 1 and Figure 3 .

[0197] [Determination of linear expansion coefficient]

[0198] The linear expansion coefficient in the plane of each liquid crystal polymer film of Examples 1 to 9 and Comparative Example 1 was measured. Specifically, the linear expansion coefficient in the plane (XY direction) of the liquid crystal polymer film was measured by TMA (thermomechanical analysis) method according to JIS K 7197. As the conditions of TMA, the temperature was raised from room temperature to 150°C at 10°C / min in a nitrogen atmosphere, the load was 10g, and the sample shape was a long strip (5mm×15mm). The results of the measurement of the linear expansion coefficient (CTE) of the liquid crystal polymer film are shown in Tables 1 and Figure 4 .

[0199] [Table 1]

[0200]

[0201] From Table 1 and Figure 3The results shown show that the MIT folding times of the liquid crystal polymer films of Examples 1 to 7 using liquid crystal polymer powders having a melt viscosity of 15 to 77 Pa·s (particularly 20 to 77 Pa·s) are 100 or more, and the folding strength is improved. Therefore, it is confirmed that these liquid crystal polymer films have sufficient flexibility to be used as base materials of flexible substrates and vibration plates.

[0202] It is understood that the MIT folding endurance of the LCP film produced in the same manner as in Example 1 using the fibrillar LCP described in Patent Document 1 is about 10 times, which is similar to that of the comparative example.

[0203] It should be noted that according to Table 1 and Figure 2 The results shown show that the melt viscosity of the liquid crystal polymer powder increases, and thus the bulk density of the liquid crystal polymer powder increases. It is believed that this is because the melt viscosity of the liquid crystal polymer powder increases, and thus the fibrous particles contained in the liquid crystal polymer powder become thinner and longer. Therefore, it is believed that the folding strength of the liquid crystal polymer film as described above is improved.

[0204] In addition, from Table 1 and Figure 4 The results shown show that the linear expansion coefficient of the liquid crystal polymer films of Examples 1 to 9 using liquid crystal polymer powders having a melt viscosity of 15 to 77 Pa·s is 20 or less.

[0205] It should be noted that by using a liquid crystal polymer film having a linear expansion coefficient similar to that of copper foil (about 18 to 20 ppm / °C) as in Examples 1 to 9, it is possible to suppress problems such as warping due to heat shrinkage in the liquid crystal polymer film bonded to the copper foil.

[0206] <Example 10>

[0207] The liquid crystal polymer film of Example 10 was prepared using the same raw materials as in Example 4. The only difference from Example 4 was that a pre-pressing process was performed as a process before hot pressing the liquid crystal polymer fiber felt formed on the electrolytic copper foil together with the electrolytic copper foil using a vacuum high-temperature pressing device. The pre-pressing process was a process of first pressing at room temperature (7 MPa, 10 seconds) and then pressing at 200°C (7 MPa, 10 seconds). Then, the same treatment as in Example 4 was performed, specifically, a heat treatment was performed using a vacuum high-temperature pressing device (manufactured by Kitagawa Seiki Co., Ltd., KVHC).

[0208] (evaluate)

[0209] The density of the fiber mats of Examples 4 and 10 was measured by the following method. In addition, the linear expansion coefficient (CTE) of the liquid crystal polymer film of Example 10 was measured by the same method as that performed on the liquid crystal polymer film of Example 4, and the MIT folding fatigue test was performed. Table 2 shows the measurement results.

[0210] (Determination of density of fiber mat)

[0211] The density of the fiber mat was calculated by measuring the weight and thickness of the liquid crystal polymer fiber mat formed on the electrolytic copper foil. Specifically, the weight of the liquid crystal polymer fiber mat was calculated by subtracting the weight of the electrolytic copper foil from the measured weight. The thickness was measured using a micrometer.

[0212] [Table 2]

[0213]

[0214] As shown in the results in Table 2, by pre-pressing, the density of the fiber mat becomes higher, thereby the linear expansion coefficient (CTE) of the liquid crystal polymer film becomes smaller. By pre-pressing, the fibrous particles of the liquid crystal polymer powder in the fiber mat, which have a long side direction in the direction along the thickness direction of the liquid crystal polymer fiber mat, are pushed to the in-plane direction of the copper foil. Therefore, in addition to the molecules constituting the blocky particles, the axes of the molecules constituting the liquid crystal polymer are oriented along the in-plane direction of the liquid crystal polymer film in the thickness direction of the liquid crystal polymer film. Therefore, in the molded liquid crystal polymer film, there is a tendency that the main orientation direction of the molecules of the liquid crystal polymer is along the in-plane direction of the copper foil, that is, the in-plane direction of the liquid crystal polymer film. As a result, the CTE of the liquid crystal polymer film of the present embodiment is reduced, and in the liquid crystal polymer film bonded with copper foil, it is possible to suppress adverse conditions such as warping caused by thermal shrinkage. In addition, it can be seen that by orienting the liquid crystal polymer film in the in-plane direction, it is expected that the number of MIT folding resistances can be improved.

[0215] <Example 11, Comparative Example 2>

[0216] (Manufacturing of Fiber Felt of Example 11 and Comparative Example 2)

[0217] The liquid crystal polymer powder (melting point 315°C) of Example 1 is used, and necessary amounts of water and ethanol are added to prepare 2.2g of liquid crystal polymer powder relative to 30L of 50wt% ethanol aqueous solution, and the slurry-like liquid crystal polymer powder is formed into a fiber felt by a papermaking method. As a papermaking machine, a square sheet making machine 2555 manufactured by Kumagai Riki Co., Ltd. is used to pick up the liquid crystal polymer powder dispersed in the dispersion medium onto a microporous sheet of a polyester mesh with a pore size of 11μm. Next, the fiber felt of Example 11 is formed on the microporous sheet by heating and drying at a temperature of 100°C using a hot air dryer. The unit area weight of the fiber felt is about 35g / m2.

[0218] The obtained fiber mat was peeled off from the microporous sheet and heated at 280°C, 320°C, and 360°C under N 2 The heat treatment was performed in the atmosphere for 1 hour. A non-oxidizing oven was used as the heating furnace.

[0219] The liquid crystal polymer powder (melting point 315° C.) of Comparative Example 1 was used to prepare a fiber mat of Comparative Example 2 in the same manner as the fiber mat of Example 11, and heat-treated at 280° C., 320° C., and 360° C. in the same manner as the fiber mat of Example 11. The breaking tensions of the fiber mats of Example 11 and Comparative Example 2 were measured by the following method. Table 3 shows the measurement results.

[0220] (Determination of breaking tension of fiber mat)

[0221] The fiber mats of Example 11 and Comparative Example 2 that were heat treated at various temperatures were measured for breaking tension. The fiber mats after heat treatment were processed into a width of 20 mm / length of 100 mm and measured using an autograph (AG-XDplus manufactured by Shimadzu Corporation). The measurement conditions were a winding speed of 0.33 mm / sec and a mode of traction with an initial length of 50 mm.

[0222] [Table 3]

[0223]

[0224] From the results shown in Table 3, it is understood that in Example 11, even if the heat treatment temperature is 280° C. which is lower than the melting point, a breaking tension of 0.8 N / 20 mm or more is obtained.

[0225] <Example 12, Example 13>

[0226] (Manufacturing of Fiber Felts of Examples 12 and 13)

[0227] When the content of zirconium oxide relative to the total amount of the liquid crystal polymer powder is defined as W (wt%), the content of zirconium oxide W of the liquid crystal polymer powder of Example 1 is 0.0219 wt%. The content of zirconium oxide W is calculated by the following method. The liquid crystal polymer powder of Example 1 is treated to remove zirconium oxide by the following method, and the content of zirconium oxide W calculated by the following method is 0.0005 wt%.

[0228] Using the liquid crystal polymer powder of Example 1 (not subjected to zirconium oxide removal treatment, subjected to zirconium oxide removal treatment), fiber mats of Example 12 (prepared using liquid crystal polymer powder not subjected to zirconium oxide removal treatment) and Example 13 (prepared using liquid crystal polymer powder subjected to zirconium oxide removal treatment) were prepared by the same method as Example 11. Instead of the heat treatment of Example 11, the entire surface of the fiber mat was subjected to light irradiation treatment using a light irradiation device (PulseForge (registered trademark) 1300 manufactured by NovaCentrix) at set voltages of 230 V, 250 V, and 270 V for 3.5 milliseconds and a table height of 10 mm.

[0229] (Method for determining residual zirconium oxide)

[0230] Disperse 40g of the liquid crystal polymer powder to be measured in 500mL of 1mol% aqua regia and let it stand for 10 minutes. Separate the powder and the solution by suction filtration. Use the filtered solution to measure with an ICP emission analyzer (ICPS-8100, manufactured by Shimadzu Corporation) to confirm whether it can be detected above the detection limit. Use the ICP standard 1000mg / LCeriptur (manufactured by MercK) to adjust the standard solution of the calibration curve. The standard solution of the calibration curve is made into 0, 0.25, 0.50, 1.0, 2.0 [mg / L]. In addition, the measurement conditions of the ICP emission analyzer are double sequential mode, high frequency output 1.2kW, plasma gas flow rate 14L / min, auxiliary gas flow rate 1.2L / min, carrier gas flow rate 0.7L / min, nebulizer coaxial type, and measurement direction horizontal. Make the detection limit below 0.02μg / L. Calculate the zirconium content per unit weight of the liquid crystal polymer powder from the concentration of the ICP solution. The following calculation formula is used to convert the amount of Zr (molecular weight 91) into ZrO 2 (Zirconium oxide) amount (molecular weight 123).

[0231] W (weight %) = (measured zirconium ion concentration of solution (g / L)) × (123÷91) × 0.5L÷40g × 100

[0232] (Method for removing zirconium)

[0233] Disperse 40 g of the prepared liquid crystal polymer powder in 500 mL of 1 mol% aqua regia and let it stand for 10 minutes. Separate the powder and the solution by suction filtration, and disperse only the powder in 500 mL of pure water. Separate the dispersed powder by suction filtration again. Repeat this operation three times, heat to 100°C on a hot plate to evaporate the water, thereby preparing a liquid crystal polymer powder from which zirconium oxide has been removed.

[0234] (evaluate)

[0235] (Determination of breaking tension)

[0236] The fiber mats of Examples 12 and 13 after the light irradiation treatment were measured for breaking tension by the above method. Table 4 shows the measurement results.

[0237] [Table 4]

[0238]

[0239] From the results shown in Table 4, it can be seen that Example 12 obtained a fiber mat having a higher breaking tension than Example 13.

[0240] (Laser processability)

[0241] The fiber mats of Examples 12 and 13 after light irradiation (the set voltage for light irradiation treatment is 230V) were laser irradiated under the following conditions for laser processing. A KrF excimer laser with a wavelength of 248nm was generated using the CoMPexPro series (manufactured by Coherent Inc.), and the generated laser was focused to an area of ​​1mm square using a reflecting lens and a focusing lens. The film was set at the focal length of the focus, and the energy of the laser was set to 150mJ / mm per irradiation (pulse). 2 Then, 7 irradiation (pulse) energy was applied. Through such laser processing, through holes were formed in the fiber mat of Example 12, and although through holes were not formed in the fiber mat of Example 13, it could be cut. From the above results, it can be seen that Example 12, which did not perform the zirconium oxide removal treatment, can be laser processed more efficiently.

[0242] In the description of the above embodiments, combinable configurations may be combined with each other.

[0243] The embodiments and examples disclosed herein are illustrative in all respects and are not restrictive. The scope of the present invention is not indicated by the above description but by the scope of claims, and is intended to include all changes within the meaning and scope equivalent to the scope of claims.

[0244] <1>

[0245] A liquid crystal polymer powder comprising fibrous particles composed of a liquid crystal polymer,

[0246] The melt viscosity of the liquid crystal polymer powder is 15 to 77 Pa·s.

[0247] <2>

[0248] The liquid crystal polymer powder according to <1>, wherein the melt viscosity of the liquid crystal polymer powder is 20 to 77 Pa·s.

[0249] <3>

[0250] The liquid crystal polymer powder according to <1> or <2>, wherein when a fiber mat is formed using the liquid crystal polymer powder and heat-treated at a temperature not higher than the melting point of the liquid crystal polymer powder, the fiber mat has a breaking tension of 1.0 N / 20 mm or more.

[0251] <4>

[0252] The liquid crystal polymer powder according to any one of <1> to <3>, further comprising a zirconium compound.

[0253] <5>

[0254] The liquid crystal polymer powder according to <4>, wherein the zirconium compound is contained in an amount of 0.001% by weight to 0.1% by weight based on the total amount of the liquid crystal polymer powder.

[0255] <6>

[0256] A method for producing a liquid crystal polymer powder, comprising:

[0257] a fine pulverizing step of pulverizing the liquid crystal polymer raw material in a state of being dispersed in liquid nitrogen to obtain granular fine pulverized liquid crystal polymer; and

[0258] A fiberizing step of crushing the finely pulverized liquid crystal polymer using a wet high-pressure crushing device to obtain a liquid crystal polymer powder;

[0259] The melt viscosity of the liquid crystal polymer raw material is 15 to 79 Pa·s.

[0260] <7>

[0261] The method for producing a liquid crystal polymer powder according to <6>, wherein the liquid crystal polymer raw material has a melt viscosity of 20 to 79 Pa·s.

[0262] <8>

[0263] The method for producing a liquid crystal polymer powder according to <6> or <7>, wherein the liquid crystal polymer raw material is particles composed of a liquid crystal polymer.

[0264] <9>

[0265] The method for producing a liquid crystal polymer powder according to any one of <6> to <8>, wherein in the fine pulverization step, the liquid crystal polymer raw material dispersed in the liquid nitrogen is pulverized using a medium.

[0266] <10>

[0267] The method for producing a liquid crystal polymer powder according to any one of <6> to <9>, wherein the melting point of the liquid crystal polymer raw material is higher than 300° C.

[0268] Prior to the fine pulverization step, a coarse pulverization step of coarsely pulverizing the liquid crystal polymer raw material is further provided.

[0269] <11>

[0270] A liquid crystal polymer powder obtained by the production method described in any one of <6> to <10>.

[0271] <12>

[0272] A liquid crystal polymer film comprising a liquid crystal polymer powder,

[0273] The liquid crystal polymer film has an MIT folding endurance of 100 times or more.

[0274] <13>

[0275] The liquid crystal polymer film according to <12>, wherein the in-plane linear expansion coefficient of the liquid crystal polymer film is 20 ppm / ° C. or less.

[0276] <14>

[0277] A fiber mat comprises a liquid crystal polymer powder, wherein the fiber mat has a breaking tension of 1.0 N / 20 mm or more when subjected to a heat treatment at a temperature below the melting point of the liquid crystal polymer powder.

[0278] <15>

[0279] The fiber mat according to <14>, wherein the density of the fiber mat is 0.1 to 1.5 g / cm 3 .

[0280] <16>

[0281] A method for manufacturing a liquid crystal polymer film, comprising:

[0282] a dispersing step of dispersing the liquid crystal polymer powder according to any one of <1> to <5> and <11> in a dispersion medium to prepare a paste or slurry;

[0283] a felting step of drying the liquid crystal polymer powder in a paste or slurry state to form a liquid crystal polymer fiber felt; and

[0284] The hot pressing step is to obtain a liquid crystal polymer film by hot pressing the liquid crystal polymer fiber mat.

[0285] <17>

[0286] The method for producing a polymer film according to <16>, wherein the felting step includes a coating step of coating the liquid crystal polymer powder in a paste or slurry state on a copper foil.

[0287] <18>

[0288] The method for producing a liquid crystal polymer film according to <17>, wherein in the heat pressing step, the liquid crystal polymer fiber mat is heat pressed together with the copper foil.

[0289] <19>

[0290] The method for producing a liquid crystal polymer film according to any one of <16> to <18>, further comprising a step of performing pre-pressing at a temperature of 220° C. or less before the heat pressing step.

[0291] <20>

[0292] The method for producing a liquid crystal polymer film according to any one of <16> to <19>, wherein in the felting step, the liquid crystal polymer powder in a paste or slurry state is formed into the liquid crystal polymer fiber felt by a papermaking method.

[0293] <21>

[0294] A liquid crystal polymer film obtained by the production method described in any one of <16> to <20>.

[0295] Explanation of symbols

[0296] 10 microporous sheet, 15 supply roller, 20 papermaking net, 25, 26 conveyor rollers, 30 fiber felt, 31 first main surface, 32 second main surface, 40 storage unit, 41 dispersion medium, 50 heating device, 60 light irradiation device, 100 papermaking machine.

Claims

1. A liquid crystal polymer powder comprising fibrous particles composed of a liquid crystal polymer, The melt viscosity of the liquid crystal polymer powder is 15 to 77 Pa·s.

2. The liquid crystal polymer powder according to claim 1, wherein The melt viscosity of the liquid crystal polymer powder is 20 to 77 Pa·s.

3. The liquid crystal polymer powder according to claim 1 or 2, wherein When a fiber mat is formed using the liquid crystal polymer powder and heat-treated at a temperature not higher than the melting point of the liquid crystal polymer powder, the fiber mat has a breaking tension of 1.0 N / 20 mm or more.

4. The liquid crystal polymer powder according to any one of claims 1 to 3, wherein Further comprising a zirconium compound.

5. The liquid crystal polymer powder according to claim 4, wherein The zirconium compound is contained in an amount of 0.001 wt % to 0.1 wt % based on the total amount of the liquid crystal polymer powder.

6. A method for producing a liquid crystal polymer powder, comprising: a fine pulverizing step of pulverizing the liquid crystal polymer raw material in a state of being dispersed in liquid nitrogen to obtain granular fine pulverized liquid crystal polymer; and A fiberizing step of crushing the finely pulverized liquid crystal polymer using a wet high-pressure crushing device to obtain a liquid crystal polymer powder; The melt viscosity of the liquid crystal polymer raw material is 15 to 79 Pa·s.

7. The method for producing a liquid crystal polymer powder according to claim 6, wherein: The melt viscosity of the liquid crystal polymer raw material is 20 to 79 Pa·s.

8. The method for producing a liquid crystal polymer powder according to claim 6 or 7, wherein: The liquid crystal polymer raw material is particles composed of liquid crystal polymer.

9. The method for producing a liquid crystal polymer powder according to any one of claims 6 to 8, wherein: In the fine pulverization step, the liquid crystal polymer raw material dispersed in the liquid nitrogen is pulverized using a medium.

10. The method for producing a liquid crystal polymer powder according to any one of claims 6 to 9, wherein: The melting point of the liquid crystal polymer raw material is higher than 300°C. Prior to the fine pulverization step, a coarse pulverization step of coarsely pulverizing the liquid crystal polymer raw material is further provided.

11. A liquid crystal polymer powder obtained by the production method according to any one of claims 6 to 10.

12. A liquid crystal polymer film comprising a liquid crystal polymer powder, The liquid crystal polymer film has an MIT folding endurance of 100 times or more.

13. The liquid crystal polymer film according to claim 12, wherein The liquid crystal polymer film has an in-plane linear expansion coefficient of 20 ppm / ° C. or less.

14. A fiber mat comprising a liquid crystal polymer powder, wherein the fiber mat has a breaking tension of 1.0 N / 20 mm or more when heat-treated at a temperature below the melting point of the liquid crystal polymer powder.

15. The fiber mat according to claim 14, wherein: The density of the fiber felt is 0.1-1.5 g / cm 3 .

16. A method for producing a liquid crystal polymer film, comprising: a dispersing step of dispersing the liquid crystal polymer powder according to any one of claims 1 to 5 and 11 in a dispersion medium to form a paste or slurry; a felting step of drying the liquid crystal polymer powder in a paste or slurry state to form a liquid crystal polymer fiber felt; and The hot pressing step is to obtain a liquid crystal polymer film by hot pressing the liquid crystal polymer fiber mat.

17. The method for producing a polymer film according to claim 16, wherein: The felting step includes a coating step of coating the liquid crystal polymer powder in a paste or slurry state on a copper foil.

18. The method for producing a liquid crystal polymer film according to claim 17, wherein: In the heat pressing process, the liquid crystal polymer fiber mat is heat pressed together with the copper foil.

19. The method for producing a liquid crystal polymer film according to any one of claims 16 to 18, wherein Prior to the hot pressing step, a step of pre-pressing at a temperature of 220° C. or less is further provided.

20. The method for producing a liquid crystal polymer film according to any one of claims 16 to 19, wherein In the felting step, the liquid crystal polymer powder in a paste or slurry state is formed into the liquid crystal polymer fiber mat by a papermaking method.

21. A liquid crystal polymer film obtained by the production method according to any one of claims 16 to 20.

Citation Information

Patent Citations

  • Output level stabilizing system

    JP1984004307A

  • Polyalkylene arylate resin composition

    JP1993125160A